The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (34th Annual Southern African Transport Conference 6-9 July 2015, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Keywords: Southern African Transport Conference; Transportation

Internal Audit Characteristics and Quality of Accounting Information in Nigeria - Ogundana, Oyebisi Mary; Ojeka, Stephen; Ojua, Michael; Nwaze, Chukwu (1st Academic Conference of Accounting and Finance, 2015)
The basic goal of Accounting is to provide enabling accounting information for reliable decision-making. The quality level of this accounting information comes from the company's governance practices, thereby emphasizing the importance of corporate governance in companies. Recently, following the financial crises resulting in accounting scandals, attention has been moving towards Internal Audit Function as an important factor in the structure of Corporate Governance. This paper therefore examined the extent of the relationship between internal audit function and the quality of accounting information of companies. The study adopted the Survey research design. The research instrument employed was Questionnaire which was administered to internal auditors of the “Big Four”. Linear regression analysis was employed in the analysis of the data collected with the use of Statistical Packages for Social Sciences (SPSS). The results revealed that there is a significant relationship between the internal audit characteristics and the quality of accounting information. It was recommended that in order to provide credibility to the financial statement, there should be a law in place mandating attachment of internal auditors report to the financial statement
Keywords: Accounting quality; Accounting report; Corporate governance; Fraud; internal auditing